Istorija srednich vekov učebnik dlja učitelʹskich institutov - Semenov, Viktor F. (Gosudarstvennoe Ucebno-Pedagogičeskoe Izdatelʹstvo Ministerstva Prosveščenija RSFSR, 1951)
The textbook contains a systematically presented course on the history of the Middle Ages from the fall of the Roman Empire to the 40s of the 17th century. The textbook is intended for students of teacher training institutes, but can also be successfully used for self-education.